PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV SD NEGERI 19 BALIK ALAM KECAMATAN MANDAU - Eltrizar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The problem in this research is the low of Civics learning outcomes in fourth grade (IV) SD Negeri 19 Balik Alam, this can be seen from the average grade, that is 66,23 (with KKM 70). The purpose of this study is to improve the results of learning Civics fourth grade students SD Negeri 19 Balik Alam with the application of quantum teaching learning model. This research is a class action research (PTK) with 2 cycles. Based on data analysis of research results after applying quantum teaching model, the average percentage of teacher activity in cycle I 66.66% increased to 85.4% in cycle II. The average percentage of student activity also increased by 56.25% in the first cycle increased to 87.49% in cycle II. Student learning outcomes on the basic score with the average class 66,23 and in the first cycle has increased with the average grade grade 71.11 with the percentage increase in learning outcomes 8.87% and the percentage of students who complete 73.07%, and on the second cycle increased again with the average class of 77.60 with the percentage increase in learning outcomes 17.16% and the percentage of students who complete 84.61%. The results of this study showed that the application of quantum teaching model can improve the learning outcomes of fourth grade students of SD Negeri 19 Balik Alam